Soil Requirements of Three Salt Tolerant, Endemic Species from South-East Spain - Antonio LIDÓN; Monica BOSCAIU; Francisco COLLADO; Oscar VICENTE (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2009)
The edaphic requirements of three endemic species from SE Spain have been investigated. Limonium dufourii is a narrow endemic,critically endangered; Thalictrum maritimum and Centaurea dracunculifolia are SE Iberian endemics, considered vulnerable and nearthreatened, respectively. The three taxa inhabit the same type of saline habitats, salt marshes called “malladas”. Several soil parameters(pH, electrical conductivity, soil chloride and sodium contents) were determined in sampling sites where plants of the selected taxa werepresent. In all the studied zones, soils are basic, with small differences in their pH. The presence of high amounts of chloride and sodiumions indicates sodic-alkaline soils, with NaCl of marine origin as the major salt. There are, however, clear differences in soil salinity, asrevealed by electric conductivity (EC) measurements. The extension and size of the populations of the three taxa, as well as their degree ofthreat, correlate with the edaphic characteristics of their habitats. Limonium dufourii, by far the scarcest and most endangered species, wasfound only in the zones with the highest soil EC, where neither of the other two taxa were present. On the other hand, C. dracunculifolia,relatively frequent and with minimal risk of extinction, tolerates a wide range of variation of electric conductivity in the soil. Thalictrummaritimum shares some of the C. dracunculifolia habitats, those with relatively higher soil salinity, and shows higher salt tolerance undercontrolled greenhouse conditions.